REFRESHING PRAKTEK PEMANTAUAN STATUS GIZI BAGI KADER POSYANDU DESA TANGKIT KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI TAHUN 2023 - Asparian, Asparian; Siregar, Sri Astuti; Lanita, Usi (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Malnutrition cases nationally are still high, namely 21.6% in 2022. Limited knowledge and skills of cadres in monitoring growth and development affect the assessment of nutritional status (PSG) in children under five. Wrong methods of measuring and using anthropometric tools will give inaccurate measurement results. The validity and reliability of the data will influence the results and policy plans chosen. Campuses and the academic community must play an active role in assisting promotive and preventive efforts to overcome public health problems.Tangkit Village, Sungai Gelam District, as an Integrated Laboratory Village (DLT), is the village at the locus of integrated stunting reduction interventions in 2022, with the highest number of stunting cases in Muaro Jambi Regency, namely 127 cases. Kader Posyandu are volunteers or volunteers who carry out activities at Posyandu. During the last four years there has never been any posyandu management training or refreshing of materials relating to PSG using anthropometric tools so that the practice of monitoring growth and development for Kader Posyandu is important. The results obtained from this service are that the majority of Kader Posyandu in Tangkit Village already have quite high knowledge, good attitudes and good PSG practice skills. There was an increase in knowledge, attitudes and practices of Nutritional Status Monitoring (PSG) among Tangkit Village Kader Posyandu after Community Service activities were carried out.